Identifikasi Jenis Mikroorganisme pada Tanaman Kurma di Kawasan Tangerang: Identification types of Microorganisms on Date palms roots in Tangerang Region - Indah Juwita SARI; Adhitya Pangestu PUTRA; Andi HARTONO; Angel Wakalingga TANZIL; Dionysius WAHYU; STEFANIE STEFANIE; YOSHUA YOSHUA; Venansi VIKTARIA; Natalya KANTANA (Biospecies, 2017)
Dates palms (Phoenix dactylifera L.) are species of plants which can be found commonly in the Middle East. The fruits are occasionally found and consumed during Ramadhan. There are several factors which can affect the growth of the plant, mycorrhiza is one of the example. Mycorrhiza is a form of mutualistic symbiosis between the root of plants and fungus. This symbiosis is proven to be favorable for plants, as it can help the absorption of the nutrient, help the defensive mechanism against pathogens, and support the plant to cope with the water deficiency. Furthermore, the plants may also have an alternate form of mutualistic symbiosis with the bacteria called endophytic bacteria which involves in the transaction of nutrient and mineral. This study requires the isolation of microorganisms that can be found within the root of date palms. The isolation can be done with the usage of Potato Dextrose Agar (PDA) as the media. There were several microorganisms which can be found within the isolated plant’s root. Through identification based on its morphology characteristics, the microorganism that was found probably are Staphylococcus; Bacillus subtillis; Glomeromycota sp., and Glomaceae sp. Keywords: Bacteria, dates, Glomaceae sp., Glomeromycota sp., mycorhizza